PENGARUH DESAIN KOMUNIKASI VISUAL AMIR TAMOREKA CENTER (ATC) TERHADAP CITRA POSITIF KANDIDAT PADA PEMILIHAN KEPALA DAERAH TAHUN 2020 KABUPATEN BANGGAI - Muhamad Ramdan; Suanti Tunggala; Ken Amasita Saadjad (KINESIK, 2022)
The purpose of the study is to find out whether the influence of visual communication design Amir Tamoreka Center (ATC) on the positive image of banggai regency election candidates with the research time carried out for three months. To collect data used questionnaires and observations. The population in this study is the people of North Luwuk District of Banggai Regency with a population of 10167 must be selected which is registered in the KPU data. The sample in the study using the Slovin formula, which is with a number of 99 must be selected according to the research object. Based on the results of research that the influence of visual communication design Amir Tamoreka Center (ATC) on the positive image of banggai regency election candidates is very good with a percentage of respondents' answers of 88.35%.